Effectiveness of current-controlled voltage source converter excited doubly fed induction generator for wind farm stabilization - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (Taylor & Francis, 2012)
In this article, stabilization methods of wind farms composed of fixed-speed wind turbines and variable-speed wind turbines are analyzed. A current-controlled voltage source converter scheme for a variable-speed wind turbine driving doubly fed induction generator is proposed. The proposed scheme is then compared with two other doubly fed induction generator control schemes to show the effectiveness of the proposed controller. Different types of symmetrical and unsymmetrical faults are analyzed considering wind farm recent grid codes. Though all of the schemes are able to stabilize the wind farms during transient conditions, the proposed current-controlled voltage source converter scheme offers the advantage of less intricacy of controller design, better performance during grid fault, and omission of DC-link protection scheme, which can reduce the overall cost of the system. Moreover, extensive simulation analyses by using PSCAD/EMTDC (Manitoba HVDC Research Center, Manitoba, Canada) are performed to determine the optimum amount of the fixed-speed wind turbine system that can be stabilized by variable-speed wind turbine system.